State, Society and International Relations in Asia - M. Parvizi Amineh (Amsterdam University Press, 2010)
This anthology brings together a series of research papers on how state and societal actors in selected Asian countries cope with external and domestic pressures to close the productivity – wealth – power gap with the high-income countries. The global context for these efforts is created by the waning of American power, and the rise of China, worldwide and even more so in Asia. The general objective of the work is to contribute to a better understanding of how local forces respond to the challenges of catch-up development, both on the domestic and global levels. The time period covered spans the colonial and post-colonial eras. The general objective has been pursued in a series of case studies of Asian countries with different historical legacies, domestic institutions and foreign policy orientations. All these countries share the objective of catch-up development, but differ in state and societal responses to the challenge of how to join the industrial division of labour from a lagging position. The contributions to this volume show how these differences affect the degree to which societies and their leaders have successfully achieved the objective of closing the power-wealth gap with countries which industrialised in the course of the nineteenth century. The book consists of 12 chapters. Following this introduction, in Chapter 1 Xiaoming Huang compares nation-state building in Japan, China and Korea and its impact on religion, family and the organisation of military power. He argues that in these countries, modernizing elites, responding to external pressure, removed intermediary power holders between state organisations and society from their position, putting state-agents in their place. The objective is to get direct access to individual households, to mobilise their labour power and religious convictions and ally these with the state as an industrial and military workforce. State creates new intermediaries between state organisation and local society. In this transition phase, these people straddle two worlds at the same time, acting under cross pressures of being a member of a local community, and at the same time operating in the capacity of civil servant.